2001
DOI: 10.1093/oxfordjournals.molbev.a003867
|View full text |Cite
|
Sign up to set email alerts
|

Numerous Gene Rearrangements in the Mitochondrial Genome of the Wallaby Louse, Heterodoxus macropus (Phthiraptera)

Abstract: The complete arrangement of genes in the mitochondrial (mt) genome is known for 12 species of insects, and part of the gene arrangement in the mt genome is known for over 300 other species of insects. The arrangement of genes in the mt genome is very conserved in insects studied, since all of the protein-coding and rRNA genes and most of the tRNA genes are arranged in the same way. We sequenced the entire mt genome of the wallaby louse, Heterodoxus macropus, which is 14,670 bp long and has the 37 genes typical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
107
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(120 citation statements)
references
References 40 publications
8
107
1
Order By: Relevance
“…These regions were sufficiently divergent in these taxa that we could not be confident of sequence homology between the divergent taxa and all other taxa. Additionally, in previous phylogenetic analyses these nine taxa have all been reported to have long branches and to have unstable phylogenetic positions (Crozier & Crozier 1993;Shao et al 2001;Nardi et al 2003a;Shao & Barker 2003;Negrisolo et al 2004). We therefore excluded these taxa from the analysis.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…These regions were sufficiently divergent in these taxa that we could not be confident of sequence homology between the divergent taxa and all other taxa. Additionally, in previous phylogenetic analyses these nine taxa have all been reported to have long branches and to have unstable phylogenetic positions (Crozier & Crozier 1993;Shao et al 2001;Nardi et al 2003a;Shao & Barker 2003;Negrisolo et al 2004). We therefore excluded these taxa from the analysis.…”
Section: Methodsmentioning
confidence: 95%
“…Composition bias and mutation saturation, particularly in third codon positions, are commonly observed for arthropod mitochondrial datasets that include taxa with deep divergence times (Shao et al 2001;Nardi et al 2003a;Shao & Barker 2003;Negrisolo et al 2004). Recent work on mammalian and avian mitochondrial genomes has shown that recoding of the third positions of codons from ACGT to purines (R) and pyrimidines (Y) can recover some signal from saturated or biased third position data Harrison et al 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial genomes of lice are highly rearranged compared with other insects [25][26][27][28][29], and these rearrangements were hypothesized to be correlated with increased substitution rates. In fact, in the human body louse (P. humanus), the mitochondrion is divided into a number of minicircular chromosomes [15,30].…”
Section: Resultsmentioning
confidence: 99%
“…However, more recent studies have exposed many exceptions to the statistical significance of differences in the relative rate of nuclear gene rearrangement (e.g., Coghlan and this prediction ( et al 1999) genome rearrangement, but in both cases no attempts at nomic lineages [e.g., within the Hymenoptera, Apocrita (Dowton and Austin 1999) and the nonhemipteran assessing the significance of any differences were made. The framework for the RGR follows that developed hemipteroids (Shao et al 2001b), and the Crustacea, Anomura (Morrison et al 2002)], leading to speculaby Tajima (1993) to assess the relative rate of nucleotide substitution between two sequences. A comparison of tion that the rate of gene rearrangement is not uniform, but may sporadically increase or decrease during evolutwo sequences can reveal only the absolute number of differences between those two sequences.…”
Section: T He Organization Of the Mitochondrial Genome Amongmentioning
confidence: 99%
“…However, more recent studies have exposed many exceptions to the statistical significance of differences in the relative rate of nuclear gene rearrangement (e.g., Coghlan and this prediction (Dowton and Austin 1999; Hickerson and Cunningham 2000; Shao et al 2001a,b;Morrison Wolfe 2002). Preliminary versions of this test have been used to compare the relative rates of mitochondrial et Shao and Barker 2002;Dowton et al 2003). Further, rearrangements appear focused in certain taxo- and nuclear (Burt et al 1999) genome rearrangement, but in both cases no attempts at nomic lineages [e.g., within the Hymenoptera, Apocrita (Dowton and Austin 1999) and the nonhemipteran assessing the significance of any differences were made.…”
Section: T He Organization Of the Mitochondrial Genome Amongmentioning
confidence: 99%